Transition to College for Students with Autism Spectrum Disorder: Needs and Facilitation Strategies. Is Virtual Reality a Useful Tool in the Transition Process? (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The number of Autism Spectrum Disorder (ASD) postsecondary students going to University is increasing. Nonetheless, these students face more difficulties than their neuro-typical peers, due to their communication and behaviour impairments. This fact is widely recognized worldwide, and there is an increasing concern in providing them with adequate support both in their transition and beyond. The purpose of this paper is twofold. Firstly, to provide an overall summary of the general requirements of ASD students in the postsecondary education transition with strategies for facilitation, and, secondly, to analyse the possibilities of Virtual Reality (VR) as a support instrument in the transition process. We rely on a brief review of the literature to summarize the main needs and current strategies. In spite of the increasing concern, there is room for establishing general protocols to help the transition process. The use VR in fulfilling this task appears limited, but it seems to be promising.